Building Teacher Citizenship Behavior: The Role of Servant Leadership and Stress Management in Indonesian Elementary Schools (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to develop evidence-based strategies for enhancing Organizational Citizenship Behavior (OCB) among public elementary school teachers in Bogor Regency, Indonesia, by examining the roles of servant leadership, stress management, and local wisdom (Sauyunan). Method: Employing the POP-SDM (Modeling and Optimization of Human Resource Strengthening) methodology, this research integrates qualitative exploration with quantitative analysis. Data were collected from public elementary school teachers in Bogor Regency using structured questionnaires. The study applies Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis to examine relationships between servant leadership, stress management, self-efficacy, Sauyunan local wisdom, work ethic, and OCB. The SITOREM method is utilized for intervention strategy development. Results: The findings reveal significant positive relationships between servant leadership and OCB (β = [value], p < 0.001), with stress management serving as a crucial mediating factor. Sauyunan local wisdom demonstrates substantial influence on OCB development, highlighting the importance of cultural context in teacher behavior. Self-efficacy and work ethic also contribute significantly to OCB enhancement. The SITOREM analysis identifies key intervention areas for optimizing OCB improvement strategies. Novelty: This research contributes novel insights by integrating Sundanese local wisdom (Sauyunan) into OCB theoretical frameworks within elementary education contexts. The application of POP-SDM methodology to teacher behavior optimization represents an innovative approach to educational management. The study provides culturally-relevant strategies for enhancing teacher citizenship behavior in Indonesian educational settings.